2022
DOI: 10.3389/fpubh.2022.937794
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported side effects of the Oxford AstraZeneca COVID-19 vaccine among healthcare workers in Ethiopia, Africa: A cross-sectional study

Abstract: IntroductionEthiopia is the second most populous country in Africa. Ethiopia received most of its COVID-19 vaccines through donations. The Oxford AstraZeneca vaccine is the first to be donated to Ethiopia by the COVAX facility. Healthcare workers were the priority population that received the Oxford AstraZeneca COVID-19 vaccine. However, there was no nationwide study on the safety of the vaccine in Ethiopia. This study aimed to measure the prevalence and predictors of self-reported side effects of the Oxford A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Similar to the findings of several published studies in Jordan or worldwide [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], the most commonly reported side effects following COVID-19 vaccination, regardless of the type of vaccine, are fatigue, fever, headache, localized pain, and myalgia. In the present study, the severity of side effects was assessed by the questionnaire.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to the findings of several published studies in Jordan or worldwide [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], the most commonly reported side effects following COVID-19 vaccination, regardless of the type of vaccine, are fatigue, fever, headache, localized pain, and myalgia. In the present study, the severity of side effects was assessed by the questionnaire.…”
Section: Discussionsupporting
confidence: 85%
“…Mallhi et al conducted a study on people with underlying diseases where the use of Pfizer vaccines was more profound [ 18 ]. Another study from Ethiopia indicated that around half of the study participants who had received AstraZeneca COVID-19 vaccines experienced at least one local and systematic side-effect [ 21 ]. The inconsistency of these results with our findings might be attributed to the disparities in the study population i.e., healthcare professionals vs. the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that most of these side-effects appeared within 6 h of vaccine administration and waned within 48 h. These results are consistent with the findings of Mallhi et al [ 18 ]. Yesuf et al reported the waning of side-effects within 72 h, and this prolonged duration might be associated with the study population [ 21 ], as healthcare professionals perform more vigilant monitoring of side-effects than the general population. It might be possible that people considered alleviating the severity of side-effects as a resolving point in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Slovakia among health workers did not differ much from what was mentioned in previous studies, where the side effects of the vaccine were injection site pain (85.2%), fatigue (54.2%), headache (34.3%), muscle pain (28.4%), and chills (26.4%) [16]. Several studies around the world nd that muscle pain in injection sites is the most prevalent side effect symptom of vaccines [17][18][19][20][21][22]. The study conducted by Zare in Iran [23] revealed that Pain and tenderness at the injection site, fever, and muscle pain are the most common side effect and this coincides with all the studies around the world that have been conducted so far among healthcare staff, which con rmed that the vaccine is safe and has no serious side effects.…”
Section: Discussionmentioning
confidence: 81%